Aphthous-Like Stomatitis in a Patient Receiving Panitumumab - Maria Kouri; Erofili Papadopoulou; Styliani Tziveleka; Dimitrios Velonis; Maria Georgaki; Evangelia Piperi; Emmanouil Vardas; Nikolaos G. Nikitakis (eJournal of Oral Maxillofacial Research)
Background: Panitumumab is an anti-epithelial growth factor receptor monoclonal antibody, approved for the treatment of metastatic colorectal cancer. Panitumumab has been more commonly associated with skin toxicity; oral adverse events have been scarcely reported in the literature. Herein, we present a case report of panitumumab-associated aphthous-like stomatitis.